2020
DOI: 10.1080/25765299.2020.1756177
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals from aqueous media by biosorption

Abstract: In this literature review, the removal of heavy metals from aqueous media by an environmentally friendly method, known as biosorption has been discussed. Biosorption can be referred to as an alternative to the common unsustainable industrial methods currently used. Removal of heavy metals from aqueous media by biosorption can take place by the aid of different types of biomass including algae, fungi, bacteria and plants. The mechanism(s) of biosorption can vary accordingly, mechanisms include physical adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(63 citation statements)
references
References 49 publications
(73 reference statements)
0
60
0
3
Order By: Relevance
“…Thus, reduction of the removal of Cu, Ni, and Pb by these bacterial strains at 37 • C might be due to a lower production of cellulose. Redha (2020) has shown that metal biosorption is not highly affected in temperatures ranging from 20 to 35 • C.…”
Section: Physicochemical Conditions Alter Metal Biosorption In Bacteriamentioning
confidence: 99%
“…Thus, reduction of the removal of Cu, Ni, and Pb by these bacterial strains at 37 • C might be due to a lower production of cellulose. Redha (2020) has shown that metal biosorption is not highly affected in temperatures ranging from 20 to 35 • C.…”
Section: Physicochemical Conditions Alter Metal Biosorption In Bacteriamentioning
confidence: 99%
“…The degree of band shifting indicates the degree of interaction of functional groups with the adsorbate ions 69 . The main content of green algae biomass surface wall are proteins, which include functional groups such as carboxyl, amines, hydroxyl and sulphate 70 , which are responsible for the metal ions biosorption onto algal biomass through ion exchange and complexation reactions. Biosorption of metal ions takes place via the ion exchange process on the cell surface 71 .…”
Section: Scanning Electron Microscopy (Sem) For Morphology Examinatiomentioning
confidence: 99%
“…Metal uptake capacity of Candida species under various experimental conditions depends on the metal type and the yeast species itself (Legorreta-Castañeda et al 2020). Bioaccumulation, which contains some processes as complex formation, ion transfer, adsorption, and chelation is applied to eliminate toxic effects of heavy metals as a cheap, efficient, and green technology (Redha 2020, Fadel et al 2017). The biosorption of metals is affected by several factors such as pH, temperature, concentration, type of biomass, contact time, and type of metal ions in solution.…”
Section: Introductionmentioning
confidence: 99%